Evaluasi Persepsi Peserta Pada Pelatihan Manajemen Proyek - Sri Mahendra Satria Wirawan (Cetta: Jurnal Ilmu Pendidikan, 2021)
Project problems such as wasted costs, poor quality, delays in completion time and other impacts that have the potential to cause legal consequences are often experienced. This happens because the implementer ignores the principles of project management in its implementation as a result of a poor understanding of project management. For this reason, the DKI Jakarta Provincial Human Resources Development Agency held a Project Management training which during the Covid-19 pandemic was conducted online. Based on the analysis carried out, from the participant aspect, it was found that the level of satisfaction of the training participants was very high to a very satisfactory level. The increase in participants' knowledge was felt to be higher by participants with a background in social education and humanities compared to participants with a science and technology background. All participants said they would apply the principles of project management because they believe their competence has increased so that they can make a positive contribution to improving the performance of their agencies. Regarding the training aspect, the material was in accordance with what was expected and needed in managing the project. This training can be attended by participants from various educational backgrounds, but the implementation time needs to be considered for participants with social and humanities backgrounds. In order to provide a better understanding, online training needs to be combined with offline in class. The training is felt to be very useful for improving the competence of project managers, so it needs to be continued with modification and development.